Neuroenhancement among Swiss Students – A Comparison of Users and Non-Users - Ott, R.; Biller-Andorno, N. (Pharmacopsychiatry, 2014)
This survey aims to contribute to the current discussion about neuroenhancement by comparing cognitive enhancer(s) (CE) users with CE non-users with a focus on their characteristics and attitudes.An online survey was sent out to all undergraduate and graduate students of the University of Zürich who allow such e-mails (n=8 642), accompanied by advertisement for the survey in lectures. 1 765 students completed the survey, which was about healthy people’s use of Ritalin, Adderall and/or Modasomil to increase concentration and/or alertness. A complementary paper-and-pencil survey (n=97 students, response rate: 95.1%) was also carried out in order to compare data.Non-therapeutic CE users (6.2%) were more often male, considered religion to be of less importance and had more experience with drugs. CE had been taken for study purposes by 4.7% of all students. CE users had tried Ritalin most often, which about half of them received from friends and colleagues. The CE users had more reasons for and fewer concerns about taking CE than non-users. The most common reasons for both groups were “the effects of learning quicker” and “for finishing more work in less time”. The most common concerns for both groups were “the worries about possible side effects” and “the goal of CE to achieve more”, and “an unnatural interference of such products with our bodies” (CE-users) or “the gut feeling of not using such products” (CE non-users).The comparison of CE users with CE non-users reveals insights about their attitudes, which will add to the understanding of why students take or could imagine taking such products.
Keywords: cognitive enhancement; ethics; questionnaire; students; Switzerland